Seroprevalence of Severe Acute Respiratory Syndrome-Coronavirus-2 Immunoglobulin M and Immunoglobulin G Antibodies among the Population of Koya University - Blbas, Safia S. I.; Ahmad, Hiwa A.; Hawezy, Dawan J.; Shawgery, Hemn; Bahadin, Hersh N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Coronavirus is a pandemic disease. In most cases, the exact infection rate cannot be determined as not everybody can be tested for the virus, even though some of them carry the virus silently. Therefore, detection of antibodies of this virus is more practical to give us a better clue about the rate of infection because the asymptomatic people can be tested too. The serological detection of anti-Severe Acute Respiratory Syndrome-Coronavirus (SARS-COV-2) antibodies among asymptomatic and moderate symptomatic individuals gives us the vital point to understanding the prevalence rate of COVID-19 among the population. Total of (436) volunteers were participated, (96) from teaching staff, (172) employee, and (168) students. Anti-SARS-COV-2 immunoglobulin G (IgG) and Immunoglobulin M (IgM) were detected in the serum by ELISA technique, and complete blood count was performed for all participants. The number of seropositive of anti-SARS-COV-2/IgG was (159), whereas IgM was (66). The highest prevalence rate of IgG detected among participants with family member infected with coronavirus (42.7%). Total WBCs count significantly increased among IgM positive participants. Many asymptomatic people were infected with coronavirus, which lead to more spreading of the virus among the population. Therefore, mass screening of the population for specific antibody against coronavirus is important to reduce the infection rate.